Retention Using Selective Hooks (RUSH) Cargo Sorting Assay for Live-cell Vesicle Tracking in the Secretory Pathway Using HeLa Cells - Pakdel, Mehrshad (Bio Protoc, 2021)
More than 30% of the total amount of proteins synthesized in mammalian cells follow the secretory pathway in order to mature and be properly sorted to their final destinations. Among several methodologies that describe live-cell monitoring of vesicles, the Retention Using Selective Hooks (RUSH) system is a powerful one that allows to visualize cargo trafficking under physiological conditions. The present protocol describes a method to use the RUSH system in live-cell microscopy and a subsequent quantitative analysis of cargo vesicles to dissect protein trafficking. In brief, HeLa cells are transiently transfected with an MMP2-RUSH construct and vesicle trafficking is evaluated by wide-field microscopy, recording videos in 1-min time frames for 45 min. We also present a quantitative approach that can be used to identify kinetics of uncharacterized protein cargo, as well as to evaluate with more detail processes such as ER-to-Golgi vesicle trafficking. Graphic abstract: [Image: see text] Live-cell RUSH: a tool to monitor real-time protein trafficking in the secretory pathway